Extensive pleural disease complicating metastatic melanoma. Issue 1 (24th February 2022) - Rajchgot, Jason; Marinescu, Daniel C.; Amjadi, Kayvan
Abstract: A 73-year old woman was referred to our interventional pulmonology clinic for diagnosis and management of a large left sided pleural effusion. Her medical history included an early stage melanoma excised from her left shoulder 1 year prior. Medical thoracoscopy was performed for simultaneous tissue diagnosis, drainage of effusion and placement of a tunneled pleural catheter. Thoracoscopy revealed innumerable, black, nodular deposits along both visceral and parietal pleural. Pathology was positive for melanoma. She had dramatic improvement in dyspnea when reassessed in clinic one week later.